Euro as a Global Currency in Relation to Dollar (Economic and Political Thought, 2014)
The main task of the work is an evaluation of the dollar and eurorelationship as the world currencies and their historical comparison. Theauthor argues that the causative factor of the appreciation trap for theBritish pound at the Bretton Woods conference was not the USA’s, asa state or national institution, choice but the Russian spying penetrationof the Roosevelt administration. At that time, Kremlin was interested inweakening the British state as a colonial power. Doing it, with the help ofH. Dexter White, a Russian spy, representing the Roosevelt administration,was a good opportunity to make progress in that field. As for the appreciationtrap for the Japanese yen at the Plaza conference, the author points outto a different but similarly effective causative factor, namely the Hayek-Friedman neoliberal doctrine that had been implemented into practice bythe Fed’s chief Allan Greenspan. The doctrine narrowed the central bankemissions of the dollar to the GDP growth. It was a kind of pathology thatopened new opportunities for the commercial banking sector to pump intofinancial markets the credit money and toxic assets playing a role of virtualquasi-commodity instruments. That was simply an improper internationalintervention. According to the author, both historical examples are no longercharacteristic of the USA political and economic system. Quite the opposite,the free trade zone between the US and EU, being an integration grouping,can be expected to introduce partnership and coordination of the dollar andeuro rates of exchange. It does not mean, however, an expansion of the euro.Objective conditions will rather favour the dollar.